Investigation of the influence of single‐particle oscillations on the transport properties of dense plasma. Issue 10 (13th July 2022) - Kodanova, Sandugash K.; Issanova, Moldir K.; Omiraliyeva, Gaukhar K.; Ramazanov, Tlekkabul S.
Abstract: Transport properties of the ionic component of dense plasmas are investigated on the basis of effective potentials taking into account the presence of an external alternating electrical (laser) field. The latter generates single‐particle oscillations of electrons and significantly changes the screening of the test charge in plasma. Therefore, transport coefficients become non‐monotonic function of the oscillation frequency. The results for the diffusion and viscosity coefficients are presented. These transport coefficients are computed using the generalized Coulomb logarithm within the Chapman‐Enskog model for the fluid description. It was revealed that the oscillation of the electrons in the alternating external field with the frequency ω ≳ 2 ω p ω 2ω_p (with ω p being plasma frequency) results in the significant reduction of the ionic diffusion and viscosity coefficients. In contrast, at ω ≲ ω p ω ω_p , the ionic diffusion and viscosity coefficients are larger compared to the case without the external field impact.